Feasibility Analysis of Boba Drink Business in Pekanbaru - Fahrozi, Muhammad; Anggraini, Nia; Nefrida; Zain, Irsyadi; Afwa, Awliya (International Journal of Managemen Analytics (IJMA), 2024)
This study aims to evaluate and analyze the feasibility of developing the Boba Drink business to minimize future risks. The research uses feasibility analysis methods focusing on market and marketing aspects, legal aspects, technical and technological aspects, financial and economic aspects, and management and human resource aspects. The study employs qualitative approaches, collecting data through market surveys, financial analysis, and expert interviews over a six-month observation period. The results indicate that the Boba Drink business is viable and feasible to run, with strong potential in the Pekanbaru market. The findings provide valuable insights for entrepreneurs and investors considering similar ventures.